Contribution of academic supervision to vocational students’ learning readiness - Suyatno Suyatno; Erlina Istiningsih; Wantini Wantini; Dian Hidayati; Astry Fajria; Siti Zulaiha (Institute of Advanced Engineering and Science, 2023)
The learning process in vocational schools has different characteristics compared to that of the non-vocational. Students’ readiness is one significant variable in determining students’ learning success. Hence, identifying the antecedent of the variable is necessary. The research aimed to measure the contribution of academic supervision through teachers' professional and pedagogic competence and its impact on vocational school students’ learning readiness. The quantitative research employed ex-post facto design with partial least square equation modelling (PLS-SEM) to test the hypothesis. Non-probability sampling, particularly purposive sampling, was used to take the samples, which were 71 teachers and 96 students in three private vocational schools in Gunung Kidul Regency, Indonesia. Meanwhile, the data were analyzed using PLS-SEM because the study involved less than 100 samples. The results showed pedagogic competence contributes to learning readiness, professional competence does not contribute to learning readiness, academic supervision contributes to pedagogic competence, and academic supervision contributes to professional competence. Besides, indirect effect scores concluded two points: academic supervision through teachers’ professional competence contributes to learning readiness and academic supervision through a teacher’s professional competence does not contribute to learning readiness. The principals and teachers can use the findings to improve their performance at school and in the classroom.